Erythrocyte membrane bioinspired near-infrared persistent luminescence nanocarriers for in vivo long-circulating bioimaging and drug delivery. (May 2018) - Liu, Jing-Min; Zhang, Dong-Dong; Fang, Guo-Zhen; Wang, Shuo
Abstract: Combination of biological entities with functional nanostructure would produce the excellent systemic drug-delivery vehicles that possess the ability to cross the biological barriers. Herein, from a biomimetic point of view, erythrocyte membrane bioinspired optical nanocarrier is fabricated by integrating Red blood cell (RBC) membrane vesicle with near-infrared persistent luminescence nanophosphors (PLNPs). The triple-doped zinc gallogermanate nanostructures with super-long near-infrared persistent luminescence (ZGGO) are used as optical emission center, mesoporous silica coated on the PLNPs (ZGGO@mSiO2 ) is employed for drug delivery, and the RBC membrane vesicle is introduced for biomimetic functionalization to ensure the developed nanocarriers bypass macrophage uptake and systemic clearance. Owing to the coating of natural erythrocyte membrane along with membrane lipids and associated membrane proteins, the proposed bioinspired nanocarriers have exhibited cell-mimicking property. Retaining the applicability of PLNPs core that favored in vitro excitation, the developed RBC-ZGGO@mSiO2 biomimetic nanocarriers have demonstrated intense fluorescence, super-long persistent luminescence, monodispersed nanosize, red light renewability, and excellent biocompatibility. In vivo mice bioimaging and biodistribution study demonstrate the erythrocyte membrane bioinspired nanoprobe loaded with doxorubicin as ideal nanocarriers for long-circulating bioimaging, in situ real-time monitoring and drug delivery. We believe the PLNPs-based biomimetic nanocarriers offer a promising nano-platform for diagnostics and therapeutics application.